2004
DOI: 10.1089/aid.2004.20.1053
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Antiretroviral Therapy in HIV-Infected Adults in Soweto, South Africa

Abstract: Little is known about achievable levels of antiretroviral treatment (ART) adherence in resource-limited settings. We conducted a cross-sectional study of adherence among patients at Chris Hani Baragwanath Hospital's Adult HIV Clinic in Soweto, South Africa. Adherence was assessed using a 1-month, self-report questionnaire and was calculated as a ratio of doses taken to doses prescribed. The 66 patients studied had a mean age of 36.1 years, a median duration of ART use of 18 months, and an overall baseline medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
163
2
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(184 citation statements)
references
References 10 publications
17
163
2
2
Order By: Relevance
“…These high levels of adherence confirm findings in other resource-limited settings (Byakika-Tusiime et al 2005;Fong et al 2003;Landman et al 2003;Laniece et al 2003;Laurent et al 2004;Laurent et al 2005a, b;Nachega et al 2004;Orrell et al 2003;Oyugi et al 2004;Remien et al 2003;Weidle et al 2002;Weiser et al 2003). Our findings contrast with those of Merenstein et al (2008), who found an inverse relationship between adherence and the number of children in the family.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…These high levels of adherence confirm findings in other resource-limited settings (Byakika-Tusiime et al 2005;Fong et al 2003;Landman et al 2003;Laniece et al 2003;Laurent et al 2004;Laurent et al 2005a, b;Nachega et al 2004;Orrell et al 2003;Oyugi et al 2004;Remien et al 2003;Weidle et al 2002;Weiser et al 2003). Our findings contrast with those of Merenstein et al (2008), who found an inverse relationship between adherence and the number of children in the family.…”
Section: Discussionsupporting
confidence: 82%
“…Provision of no-cost therapy to all eligible HIV-infected individuals in the household ensured sustained adherence. As has been reported in other studies (Mills et al 2006a;Nachega et al 2004;Weiser et al 2003), perceived stigma was commonly reported as a barrier to access and adherence to ART.…”
Section: Qualitative Findingssupporting
confidence: 72%
See 1 more Smart Citation
“…39 Failure to disclose one's HIV status to a partner is associated with stigma, which has been shown to hinder adherence. 4 A study in India found that reminders from family members, an indirect indicator that disclosure had occurred, were associated with better adherence outcomes. 40 Provision of couple HIV counseling and testing and community education encouraging disclosure may improve adherence.…”
Section: Discussionmentioning
confidence: 99%
“…1 Most formal evaluations have been of ART programs in large urban hospitals 2 or from donor-funded homebased programs. 3 Antiretroviral therapy adherence has also been reported predominantly among patients in the context of urban [4][5][6] and research settings. 7 Few studies have evaluated government-based ART programs, serving rural populations where the structural-and patient-level barriers to successful treatment response are unique.…”
Section: Introductionmentioning
confidence: 99%